Ranula – A Case Report - Shobha Bijjaragi; Ashwini Rani SR; Varsha A Sangle; Girish Suragimath (Journal of Krishna Institute of Medical Sciences University, 2015)
The term ranula is derived from a latin word “rana” which means “frog.” Ranula is a mucous containing swelling that occurs in the floor of the mouth. It usually presents as a well circumscribed, soft, bluish swelling covered by a thin layer of epithelium. This article presents a case of simple ranula in seven year old female patient treated with excision of sublingual gland.